Individual commitment and team performance : evidence from mutual fund managers - Luo, Jiang (2021)
The psychology literature suggests that individual commitment has a positive effect on team performance by mitigating the free-rider problem. With its detailed management-team information, the mutual fund industry provides a unique opportunity to study how individual managerial commitment is related to performance. Committed fund managers are defined as those who work only for one fund. With few incentives to acquire private information, teams with no committed members underperform those with committed members. These findings remain robust after we incorporate various controls. We also explore why non-committed teams have been used increasingly often despite their poor performance.